Promotion and experiential marketing on purchasing decisions mediated by e-WOM in coffee SMEs - Hamdani, Nizar Alam; Widiasih , Noviearti; Gumilar, Irfan Rizki; Herlianti, Anggun Oktavia; Setiana, Soni Mulyawan (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study aimed to determine the effect of promotion and experiential marketing on buying decisions mediated by electronic Word-of-Mouth (e-WOM) in coffee SMEs. This research is quantitative research by distributing questionnaires. The research sample is 100 respondents with the Cochran formula. Data collection in this study used an ordinal and was measured using a Likert scale. Data analysis was carried out using SEM-PLS with the help of smart PLS. The results of the study indicate that purchasing decisions are significantly impacted by experiential marketing. It demonstrates how experiential marketing's sense, feeling, thinking, acting, and relating components are frequently used by marketers to influence consumer decisions. e-WOM marketing is significantly impacted by experiential marketing. It demonstrates that experience marketing impacts coffee SMEs' use of e-WOM marketing.